MULTILINGUALISM PORTRAYED IN CODE SWITCHING PRACTICE OF TIMORESE: ETHNICITY AND IDENTITY - Arcenia Maria Martins; Emy Sudarwati (LLDIKTI Wilayah X, 2023)
This study aims to investigate three issues namely (1) the types of code switching practiced by Timorese, (2) the factors influencing their multilingualism, and (3)the reasons of Timorese to choose Portuguese over Bahasa Indonesia as the official language.The information was gathered through questionnaires and in-depth interviews, and it was evaluated using Holmes’s code-switching theories. The current study finds that the Timorese mostly used metaphorical code-switching. This happens due to a paucity of vocabulary in Tetum, which lead to lexical borrowing and the adoption of Portuguese words into Tetum and lead Timorese unwittingly flip metaphorical codes. Additionaly, the country’s many languages cause a metaphorical code-switching among the speakers. Furthermore, this study also reveals that multilingualism and the phenomenon of code-switching in Timor-Leste are influenced by colonization, geographical factor, television shows, social media and mix marriages. Lastly, Portuguese is chosen as the official language due to prolonged colonialization and occupation.